1998
DOI: 10.4315/0362-028x-61.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hot Water for Beef Carcass Decontamination

Abstract: Hot water treatment of beef carcass surfaces for reduction of Escherichia coli O157:H7, Salmonella typhimurium, and various indicator organisms was studied using a model carcass spray cabinet. Paired hot carcass surface regions with different external fat characteristics (inside round, outside round, brisket, flank, and clod) were removed from carcasses immediately after the slaughter and dressing process. All cuts were inoculated with bovine feces containing 10(6)/g each of rifampicin-resistant E. coli O157:H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 0 publications
3
53
1
Order By: Relevance
“…Compared with the lactic acid wash, the hot water wash reduced APC by an additional 1.1 log CFU and EBC by an additional 1.7 log CFU. In previous studies of hot water washes of postevisceration carcasses and chilled beef, similar reductions have been obtained: 2.1 to 2.9 log CFU for APC (11,17) and 2.7 to 3.3 log CFU for coliforms (10, 11), a group that represents the majority of Enterobacteriaceae on carcass surfaces (9).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Compared with the lactic acid wash, the hot water wash reduced APC by an additional 1.1 log CFU and EBC by an additional 1.7 log CFU. In previous studies of hot water washes of postevisceration carcasses and chilled beef, similar reductions have been obtained: 2.1 to 2.9 log CFU for APC (11,17) and 2.7 to 3.3 log CFU for coliforms (10, 11), a group that represents the majority of Enterobacteriaceae on carcass surfaces (9).…”
Section: Resultsmentioning
confidence: 60%
“…The surface temperature of 70ЊC resulted in a 2.0-log reduction in APC and a 2.7-log reduction of coliforms (19). The surface temperature of 82ЊC resulted in a 4-to 4.9-log reduction of bacteria (11). The hot water wash cabinet used for preevisceration carcasses in our experiments applied 74ЊC water for 5.5 s. This treatment raised the carcass surface temperature to 70ЊC for 3.5 s and reduced both APC and EBC by 2.7 log CFU/100 cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Colonies of pathogens were differentially counted after 24 h incubation at 35°C. Salmonella enterica colonies are distinguished from E. coli O157:H7 colonies through appearance of blackened centers resulting from sulfite reduction, as well as through E. coli fermentation of lactose, producing yellow-tinted haloes (Castillo et al, 1998).…”
Section: Preparation Of Microorganisms For Inoculation Onto Spinach Smentioning
confidence: 99%
“…Decontamination treatments of hides (Castillo et al, 1998a;1998b;McEvoy et al, 2001;Bosilevac et al, 2005) and dressed carcasses (e.g. steam vacuuming, steam pasteurization, hot water washes, organic acid washes, etc.)…”
Section: Decontamination Treatmentsmentioning
confidence: 99%
“…Hot water (74-80ºC) 3.7 log reduction Castillo et al 1998b Steam pasteurization (above atmospheric pressure) 3.7 to 4.4 reduction Phebus et al 1997 assessors and risk managers need to ensure any such substance is fi rst shown to be safe and effective at signifi cantly reducing microbial contamination before it can be approved. In addition, EU authorities (e.g.…”
Section: Decontamination Treatmentsmentioning
confidence: 99%